Respuesta :
It
is given that ∠B ≅ ∠C. Assume AB and AC are not congruent. If AB >
AC, then m∠C > m∠B by the triangle parts relationship theorem. If AC > AB, then m∠B > m∠C for
the same reason.
However, using the given statement and the definition of congruency, we know that m∠B = m∠C.
Therefore, AB = AC and AB ≅ AC.
However, using the given statement and the definition of congruency, we know that m∠B = m∠C.
Therefore, AB = AC and AB ≅ AC.
Answer:
Its converse of the triangle parts relationship theorem